2006
DOI: 10.1128/jcm.44.5.1711-1718.2006
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Release by Aspergillus fumigatus of Galactofuranose Antigens, 1,3-β- d -Glucan, and DNA, Surrogate Markers Used for Diagnosis of Invasive Aspergillosis

Abstract: Aspergillus markers are becoming increasingly important for the early diagnosis of invasive aspergillosis. The kinetics of release of these surrogate markers, however, is largely unknown. We investigated the release of ␤-(1-5)-galactofuranosyl (galf) antigens (Platelia Aspergillus), 1,3-␤-D-glucan (BG) (Fungitell), and DNA (PCR) in an in vitro model of Aspergillus fumigatus. The results showed that release is correlated to the growth phase of the fungus, which depends on available nutrients. Whereas galf antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
38
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 57 publications
5
38
0
2
Order By: Relevance
“…By degrading GM epitopes, the enzyme may interfere with the immunoassay by blocking the antigen-antibody complex formation. The demonstration that A. fumigatus produces 2-20% of the β-D-galactofuranosidase produced by A. niger 6 suggests that A. fumigatus could react more avidly in the GM EIA test than A. niger, as found in the current study. The influence of the β-D-galactofuranosidase on GM levels is not completely clear, since similar enzyme activity has been observed for patients with IA caused by A. fumigatus in spite of serum GM levels 5 .…”
Section: Discussionsupporting
confidence: 67%
“…By degrading GM epitopes, the enzyme may interfere with the immunoassay by blocking the antigen-antibody complex formation. The demonstration that A. fumigatus produces 2-20% of the β-D-galactofuranosidase produced by A. niger 6 suggests that A. fumigatus could react more avidly in the GM EIA test than A. niger, as found in the current study. The influence of the β-D-galactofuranosidase on GM levels is not completely clear, since similar enzyme activity has been observed for patients with IA caused by A. fumigatus in spite of serum GM levels 5 .…”
Section: Discussionsupporting
confidence: 67%
“…circulate in the blood. Of note, many studies suggest that most of the circulating Aspergillus DNA is present not in the form of conidia but rather as free DNA (67,68). This provides an explanation for the fact that blood cultures have such a low sensitivity for aspergillosis (69), as well as our finding that whole-blood testing is not superior to serum testing.…”
Section: Discussionsupporting
confidence: 49%
“…A previous study has shown that GM is released during active growth of Aspergillus fumigatus, whereas DNA is released through hyphal damage autolysis or host defenses and will not be released concomitantly with GM (19). The extracellular glycoprotein targeted by the LFD is also released during active hyphal growth, and greater concordance with GM positivity could be predicted (11).…”
Section: Discussionmentioning
confidence: 86%